Can cholinium chloride form eutectic solvents with organic chloride-based salts? - Abranches, Dinis O. (2018)
The high melting point of a large number of organic salts with potential ionic liquid-like properties, hinders their applicability as solvents. Considering the success of cholinium chloride on lowering the melting temperature of several substances and its success on forming deep eutectic solvents, this work studies its mixing with organic chlorides to lower their melting points producing eutectic ionic liquids. The solid-liquid phase diagrams for binary mixtures composed of cholinium chloride and ten organic halides were experimentally measured. Surprisingly, cholinium chloride presented, for all these systems, significant positive deviations from ideal liquid behaviour that restricted its ability to lower the melting points of these mixtures. Only for mixtures with ammonium chloride, tetramethylammonium chloride, bis(2-hydroxyethyl)dimethylammonium chloride or cholinium bromide was cholinium chloride able to significantly lower the melting point of the mixture, but without reaching values close to room temperature (298 K). For a better understanding of the results obtained, the solid-liquid phase diagrams of four alkylammonium chloride-based mixtures were experimentally assessed and used to show that these compounds are better than cholinium chloride at inducing negative deviations from ideality, leading to greater melting point depressions.